Enhancing Entrepreneurial Interest among Islamic Boarding School Vocational Students through a Digital Entrepreneurship-Based Digital Marketing Learning Model - Sutadi Sutadi; Sunhaji Sunhaji; Fathul Aminudin Aziz (STAI Hubbulwathan Duri, 2023)
Current approaches to digital marketing education in Islamic boarding school-based vocational schools demonstrate significant limitations in fostering entrepreneurial interest among students. This research aims to develop and evaluate a digital marketing learning model tailored to enhance digital entrepreneurship and increase students' entrepreneurial interest in these institutions. Employing a Research and Development (RD) methodology, the study sampled three vocational schools using the Slovin formula and custom random sampling in 11th-grade Marketing classes. Data were collected through observations, interviews, questionnaires, tests, and documentation. Descriptive statistical analysis, including percentage, categorization, and narrative descriptive techniques, was utilized for data analysis. The findings indicate that current digital marketing education is suboptimal in stimulating entrepreneurial interest. Furthermore, the study reveals deficiencies in learning planning and a lack of effective learning models focused on digital entrepreneurship.